The Double-Faceted Universal Consciousness Reality: A Theoretical Review (Global Journal of Science Frontier Research, 2018)
Introduction-Twenty First Century Physics is being metamorphosed by the discovery of the Computational Unified Field Theory" (CUFT), i.e. from its "old" "Material-Causal" Paradigm to the CUFT's newly discovered "Universal Consciousness Reality's 'ACausal Computation' Paradigm! Hence, The purpose of this last article within this Special Issue is to summarize and encapsulate the far reaching theoretical implications of the CUFT's new Universal Consciousness Reality which replaces and transcends Relativity Theory (RT) and Quantum Mechanics (QM): As described extensively in the fourteen articles within this Special Issue (and previously: Bentwich: ???) the empirical validation of at least one of the Computational Unified Field Theory's (CUFT) "differential-critical predictions", e.g., associated with the "Proton-Puzzle" findings, alongside its resolution of the principle (apparent) theoretical inconsistency between RT and QM; as well as of a series of unresolved "Physical Conundrums" (e.g., such as "Dark-Energy" and "Dark-Matter", the "Arrow of Time" etc.)